Development of an Intelligent Surface Plasmon Resonance Based Sensor: practical examples - Oliveira, Leiva C.; Saraiva, José G. O.; Araújo, Silvio R. F. de; Melo, Arthur A. de; Lima, Antonio M. N. (Anais do Workshop Brasileiro de Engenharia de Software Inteligente (ISE), 2025)
Intelligent sensors based on Surface Plasmon Resonance (SPR) require careful integration of the artificial intelligence (AI) capabilities into the operational aspects of measurement, with the development of new tasks, activities, software, processes, or services. This paper presents practical examples of AI interventions for the construction of smart SPR sensors built with the PPBIO prism.